Gamification-Based Sharia Personal Financial Management: An Innovation to Improve Financial Literacy and Behavior of the Younger Generation - Putra Budiman; Friska Anggi Siregar; Nurjanah (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
The low level of Islamic financial literacy among the younger generation presents a challenge in realizing financial behavior in accordance with Islamic principles in the digital era. This study aims to analyze the effectiveness of this approach.gamification in improving Sharia-based personal financial literacy and behavior. The method used isSystematic Literature Review(SLR)with guidelinesPRISMA 2020, which involved an analysis of 25 Scopus-indexed articles from 2020–2025. The results showed that gamification can increase intrinsic motivation, user engagement, and understanding of Islamic finance concepts such as contracts, usury, and halal fund management. Gamification elements such asprogress tracking,leaderboard, Andinteractive simulationIt has been proven to be more effective than conventional educational methods in developing disciplined, transparent, and sharia-compliant financial behavior. Consequently, gamification can be an innovative strategy for educational institutions and the financial industry.sharia fintech, and the government in expanding inclusion and Islamic financial literacy among the younger generation of Muslims.